Reseña del libro "Economía de la Educación" de Antonio Cabrales e Ismael Sanz (Coordinadores) - Faci Lucia, Fernando (Avances en Supervisión Educativa, 2024)
The book "Economía de la Educación" coordinated by Antonio Cabrales and Ismael Sanz, with the collaboration of 22 researchers, offers a comprehensive and updated overview of the current state of knowledge in this field of research. As noted in the synopsis available on the Ramón Areces Foundation's website, this manual integrates "comparative analyses of the Spanish and European educational systems with advanced economic and econometric approaches to evaluate and suggest effective educational policies." Thus, we have a book intended to be used as a reference for education professionals and as a complementary academic manual for use in the university setting.